Taylor's Series and Dispersion Relation Analyses of the Vector Pion Form Factor and their Comparison with Perturbative and Non Perturbative Calculations - Tran, Truong Nguyen (Communications in Physics, 2015)
The first three coefficients of the Taylor's series expansion of the vevtor pion form factor as a function of the momentum transfer are evaluated using the experimental data on the pion form factor and the P-wave \(ππ\) phase shifts. The real part of the form factor as a function of energy is also calculated by dispersion relation. Comparisons there results with Chiral Perturbation Theory and unitarized models are given